The Effect of Lockdown Due to the COVID-19 Pandemic on Digital Eye Strain Symptoms Among the General Population: A Cross-Sectional Survey - Abusamak, Mohammad; Jaber, Hatim M.; Alrawashdeh, Hamzeh Mohammad (Frontiers in Public Health, 2022)
Repetitive prolonged use of digital devices without regular breaks has detrimental effects on ocular health and quality of vision. Individuals with chronic eye problems and refractive errors are at higher risk of developing digital eye strain (DES). Correction of refractive errors, adopting healthy practices will reduce its risk. The survey examined the effect of prolonged lockdown on the development and increased severity of digital eye strain (DES) symptoms among the general population. An online survey was conducted in March 2020 on social media platforms in Jordan. Data from 1,460 responders were analyzed. About half of the respondents were between 30–49 years, 28.4% were retired, 21% had chronic systemic illness, and 23% reported chronic eye problems. A rise in the use of digital devices during lockdown was reported by 957 participants, with 33% of them used digital devices more than 4 h a day. The most common symptoms before and during lockdown were headache and neck / shoulder pain have the highest associations (X2 = 280.0, 271.3, df = 4, p < 0.001 respectively). Female gender, existence of chronic eye problems and systemic diseases, and duration of using digital devices were found to be statistically significant factors associated with increasing severity of eye symptoms during lockdown. Not taking enough regular breaks from digital devices showed significant association with blurred vision at distance and near (X2 = 13.03, 10.74, df = 4, P = 0.011, 0.03, respectively). People with chronic eye problems and increased time using devices during lockdown developed new eye complaints three times more than before the lockdown and males were two times more likely than females to have more severe eye symptoms.